Role of parenteral iron sucrose in the treatment of iron-deficiency anemia in pregnant women of gestational age 20–34 weeks - T Deepthisri; N Chaitanya; Rohin (MRIMS Journal of Health Sciences, 2023)
Background: Anemia is responsible directly or indirectly for 40%–60% of maternal deaths from cardiac failure, hemorrhage, infection, and preeclampsia. It also increases perinatal mortality and morbidity rates consequent to preterm deliveries, intrauterine growth restriction, low iron stores, iron-deficiency anemia, and cognitive and affective dysfunction in the infant. Objective: The objective of this study is to study the efficacy of intravenous iron sucrose in terms of hemoglobin rise and side effects. Materials and Methods: Single-center, hospital-based comparative prospective study was conducted among 60 patients admitted with anemia in pregnancy with a hemoglobin concentration of 7.5–9 g/dl. Blood samples were sent for evaluation of hemoglobin, packed cell volume (PCV), and serum ferritin levels at baseline, at 4, and 8 weeks. Results: Mean age was 29.08 ± 5.74 years. About 51.7% belonged to the middle social class. Most were gravida III (36.7%). About 46.7% had 20–24 weeks of gestations. Seventy-five percent had microcytic hypochromic anemia. Hemoglobin improved significantly (P < 0.05) from 8.76 ± 0.54 g% at baseline to 11.47 ± 0.85 g% at 4 weeks, and to 12.68 ± 1.04 g% at 8 weeks; PCV also improved significantly (P < 0.05) from 26.78 ± 3.11% to 34.64 ± 3.73% at 4 weeks and again improved to 42.50 ± 4.67% at 8 weeks; serum ferritin also improved significantly (P < 0.05) from 23.06 ± 7.96 μg/l to 28.86 ± 9.79 μg/l at 4 weeks and again improved to 36.31 ± 12.53 at 8 weeks after parenteral iron sucrose therapy. Only one pregnant woman complained of vomiting and only four women complained of pain at the site of injection after giving parenteral iron sucrose therapy. About 91.6% of the women had no complaints. Conclusion: Parenteral iron sucrose therapy in pregnant women with a gestational age of 20–34 weeks with iron-deficiency anemia was found effective in improving the hemoglobin, PCV, and serum ferritin with negligible side effects.